Kecerdasan Buatan dan Keamanan Manusia: Implikasi Konflik Internal dan Eksternal dalam Bidang Keamanan dan Pertahanan - Rachmasari Nur Al-Husin (Andalas Institute of International Studies UNAND, 2025)
The development of Artificial Intelligence (AI) has brought significant impacts across various aspects of life, including security and defense. AI offers the ability to enhance operational effectiveness through automation and advanced data analysis. However, its application also presents risks, particularly conflicts involving civilian populations. This research aims to analyze the implications of AI in the field of security and defense on potential conflicts using a human security approach. This approach highlights three fundamental components of human security: freedom from fear, sustainable livelihoods, and the assurance of human rights. The research employs a qualitative method with data collection techniques through literature reviews. Analysis is conducted using the illustrative method. The research finds that the use of AI in autonomous weapons often results in unintended civilian casualties, triggering external conflicts. On the other hand, technologies like face recognition and surveillance capitalism create internal conflicts due to algorithmic discrimination and privacy violations. The findings indicate that AI, while offering operational benefits, can introduce new threats in the form of digital technology threats. Therefore, it is crucial to integrate human security principles into the development and implementation of AI to minimize the risks of conflict and ensure a more responsible application of technology.